Prinsip Komunikasi Perspektif Al-Quran dalam Bahasa Jurnalistik - Imaduddin, Muhammad (Prophetica : Scientific and Research Journal of Islamic Communication and Broadcasting, 2019)
This research aims to find the suitability between the principles of journalistic language in general and the principles of communication from the perspective of Islamic teachings as stated in the Quran. The method used in this research is a qualitative method with a descriptive approach, while the paradigm used is the constructivistic paradigm. The type of this research is a literature study. There are at least 6 principles of communication from the perspective of the Quran called qaulan, namely sadidan, balighan, masyuran, layyina, marufan and kariman. This research is expected to be a reference in studying Islamic communication science in particular and communication science in general, Islamic journalism science in particular and journalism science in general and mass communication science which is the parent of journalism science.